2013
DOI: 10.1002/jcp.24244
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of placenta growth factor expression by oncostatin M in human rheumatoid arthritis synovial fibroblasts

Abstract: Oncostatin M (OSM) belongs to IL-6 subfamily and is mostly produced by T lymphocytes. High levels of OSM are detected in the pannus of rheumatoid arthritis (RA) patients and it may arouse the inflammation responses in joints and eventually leads to bone erosion. Placenta growth factor (PLGF) is an angiogenic factor and highly homologous with vascular endothelial growth factor (VEGF). It has been recently reported that PLGF is highly expressed in synovial tissue and enhances the production of proinflammatory cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 47 publications
2
11
0
Order By: Relevance
“…Of interest, adenosine and classical ischemic preconditioning have been shown to induce crosstalk 30 , 31 . Our results are in accordance with those of Tu et al who showed that expression of a dominant-negative AKT or inhibition of PI3K with LY294002 decreased STAT3 phosphorylation at both tyr705 and ser727 residues in response to oncostatin M, a cytokine of the STAT3 activating interleukin-6 family 32 . Whether propofol activates STAT3 as a single event at level of plasma membrane or via receptor internalization that links with prosurvival PI3K-AKT signaling is the subject of ongoing investigation by our laboratory.…”
Section: Discussionsupporting
confidence: 92%
“…Of interest, adenosine and classical ischemic preconditioning have been shown to induce crosstalk 30 , 31 . Our results are in accordance with those of Tu et al who showed that expression of a dominant-negative AKT or inhibition of PI3K with LY294002 decreased STAT3 phosphorylation at both tyr705 and ser727 residues in response to oncostatin M, a cytokine of the STAT3 activating interleukin-6 family 32 . Whether propofol activates STAT3 as a single event at level of plasma membrane or via receptor internalization that links with prosurvival PI3K-AKT signaling is the subject of ongoing investigation by our laboratory.…”
Section: Discussionsupporting
confidence: 92%
“…5b). The latter observation is consistent with a recent study which showed that STAT3 activity induces PlGF gene expression in synovial fibroblasts [44]. Inhibition of the NF-jB activity induced a delayed increase of the PlGF gene expression under control conditions (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…Fibroblasts are also a source of PlGF in other pathological conditions such as rheumatoid arthritis [26]. In addition to fibroblasts, PlGF expression has also been detected in cultured endothelial cells whereas monocyte/macrophage lineage cells are not known to produce PlGF [27].…”
Section: Resultsmentioning
confidence: 99%